Peran Kebudayaan dalam Menguatkan Kerukunan Antarumat Beragama di Sidamanik, Kabupaten Simalungun - Tifani, Tamara Dilla; Ar Rahma, Maulida; Patikasari, Cindy; Guru Singa, Maratus Soleha; Muktarruddin, Muktarruddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Sidamanik is one of the areas in Simalungun Regency, North Sumatra province. This area is located between two cultures, Islam and Christianity. The livelihood of Sidamanik residents is farming, such as rice, corn, and coffee. In addition, Sidamanik also has a very large tea plantation, which is a attraction for tourists. In terms of religious harmony, Sidamanik still maintains its culture and customs according to their respective beliefs.